2021
DOI: 10.3390/ijms22031026
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Influence in Hematological Malignancies: From Genesis to Cure

Abstract: Hematological malignancies, including multiple myeloma, lymphoma, and leukemia, are a heterogeneous group of neoplasms that affect the blood, bone marrow, and lymph nodes. They originate from uncontrolled growth of hematopoietic and lymphoid cells from different stages in their maturation/differentiation and account for 6.5% of all cancers around the world. During the last decade, it has been proven that the gut microbiota, more specifically the gastrointestinal commensal bacteria, is implicated in the genesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 194 publications
(234 reference statements)
0
31
0
4
Order By: Relevance
“…The studies that addressed GM modifications during chemotherapy for childhood AL have identified antibiotics, immunosuppression, dietary changes and direct toxicity among the contributing factors to intestinal ecosystem alterations [20][21][22] (table 1). GM diversity decreases significantly after intensive induction and reinduction protocols, with a slight rebound in the time period after recovery from induction 23 .…”
Section: Gut Microbiome Modifications During Chemotherapymentioning
confidence: 99%
“…The studies that addressed GM modifications during chemotherapy for childhood AL have identified antibiotics, immunosuppression, dietary changes and direct toxicity among the contributing factors to intestinal ecosystem alterations [20][21][22] (table 1). GM diversity decreases significantly after intensive induction and reinduction protocols, with a slight rebound in the time period after recovery from induction 23 .…”
Section: Gut Microbiome Modifications During Chemotherapymentioning
confidence: 99%
“…In a large number of clinical trials CAR T cell targeting tumor-associated antigens have been found cause damage to normal tissue with low expression of tumor-associated antigens during the process of recognizing and killing tumor cells, which is referred to as the off-target effect ( 25 ). Moreover, the reasons behind the success of CAR T cells in the treatment of hematologic tumors is that they can migrate in blood, lymph nodes, and bone marrow to interact with cancer cells ( 26 ). By dynamic imaging microscopy on fresh tumor slices from nine patients, Donnadieu et al.…”
Section: Current Roadblocks In Car-t Cell For Solid Tumorsmentioning
confidence: 99%
“…Several studies indicate the implication of altered microbiome (dysbiosis) in different metabolic disorders (diabetes, obesity) [36][37][38] , inflammatory bowel disease 39-41 autism [42][43][44] , and neurodegenerative diseases Parkinson's disease [45][46][47][48] , Alzheimer disease 49,50 multiple sclerosis [51][52][53] . Recent scientific advances have significantly contributed to our understanding of the complex connection between the microbiome and cancer, solid tumors, and hematological malignancies alike [54][55][56][57] . As it appears in the literature, microorganisms and microbial elements such as lipopolysaccharides (LPS) can up-regulate Toll-like Receptors (TLR)s, which can provoke activation of nuclear factor-kB (NF-kB), which is critical for controlling tumor-associated inflammation 58,59 , invasion, growth, survival, and immunosuppression 60 .…”
Section: Antibiotic Classesmentioning
confidence: 99%